Perancangan Interior Lego Day Care Centre di Surabaya - Fransiscus Alvian Tanjaya; mariana wibowo (Intra, 2014)
With the increased economies of many working parents. As a result of normal family life becomes hampered, especially the attention to children - children that they need a day care. Facilities provided are a play area , study area , sleeping area , a library , cafeteria , office manager , laundry , and so on . Interior design of day care centers that use more colors - basic color such as red , blue , green , yellow are also the colors that are used on the game lego is a project concept . As for the formation of more designs using geometric formations , as well as helping the child to recognize shapes . Lego day care center is expected to help facilitate the development of children and parents who work.